Neuroprotective Effect of Wharton’s Jelly-Derived Mesenchymal Stem Cell-Conditioned Medium (WJMSC-CM) on Diabetes-Associated Cognitive Impairment by Improving Oxidative Stress, Neuroinflammation, and Apoptosis - Zohre Aghaei; Narges Karbalaei; Mohammad Reza Namavar; Masoud Haghani; Mahboobeh Razmkhah; Mahdi Khorsand Ghaffari; Marzieh Nemati (Stem Cells International)
According to strong evidence, diabetes mellitus increases the risk of cognitive impairment. Mesenchymal stem cells have been shown to be potential therapeutic agents for neurological disorders. In the current study, we aimed to examine the effects of Wharton’s jelly-derived mesenchymal stem cell-conditioned medium (WJMSC-CM) on learning and memory, oxidative stress, apoptosis, and histological changes in the hippocampus of diabetic rats. Randomly, 35 male Sprague Dawley rats weighing 260–300 g were allocated into five groups: control, diabetes, and three diabetic groups treated with insulin, WJMSC-CM, and DMEM. The injections of insulin (3 U/day, S.C.) and WJMSC-CM (10 mg/week, I.P.) were done for 60 days. The Morris water maze and open field were used to measure cognition and anxiety-like behaviors. Colorimetric assays were used to determine hippocampus glutathione (GSH), malondialdehyde (MDA) levels, and antioxidant enzyme activity. The histopathological evaluation of the hippocampus was performed by Nissl staining. The expression levels of Bax, Bcl-2, BDNF, and TNF-α were detected by real-time polymerase chain reaction (RT-PCR). According to our findings, WJMSC-CM significantly reduced and increased blood glucose and insulin levels, respectively. Enhanced cognition and improved anxiety-like behavior were also found in WJMSC-CM-treated diabetic rats. In addition, WJMSC-CM treatment reduced oxidative stress by lowering MDA and elevating GSH and antioxidant enzyme activity. Reduced TNF-α and enhanced Bcl-2 gene expression levels and elevated neuronal and nonneuronal (astrocytes and oligodendrocytes) cells were detected in the hippocampus of WJMSC-CM-treated diabetic rats. In conclusion, WJMSC-CM alleviated diabetes-related cognitive impairment by reducing oxidative stress, neuroinflammation, and apoptosis in diabetic rats.